Undeveloped and developed phases in the centennial evolution of a barrier-marsh-lagoon system: The case of Long Beach Island, New Jersey - Tenebruso, Christopher; Nichols-O’Neill, Shane; Lorenzo-Trueba, Jorge; Ciarletta, Daniel J.; Miselis, Jennifer L. (Frontiers in Marine Science, 2022)
Provisionally accepted: The final, formatted version of the article will be published soon